Institutional structure of financial regulation : theories and international experiences - Huang, Robin Hui; Schoenmaker, Dirk (London : Routledge, 2015)
"Institutional structure of financial regulation is currently a subject of significant academic and practical interest, in light of the ongoing global financial crisis. The financial crisis has called into question the adequacy of financial regulation at the national and supranational levels. Financial regulatory structure has now been considered a key issue behind the financial crisis and as such, a wave of financial regulatory reform has ensued in major markets overseas, including the enactment of the Dodd-Frank Act in the US and the program to split the Financial Services Authority in the UK. Mainland China and Hong Kong are no exceptions. In Hong Kong, the much-publicized Lehman Brothers minibond saga has prompted the Hong Kong government to reconsider its financial regulatory regime. Likewise, the Mainland has recently staged a reshuffle at the top financial regulators.This book examines the institutional structure reform of financial regulation presently going on at the international level, and the resulting policy implications for the local reforms in Hong Kong and Mainland China. The book will consist of three parts the first of which explores the theory of financial regulatory structure, the second considers international perspectives on financial regulatory structures, and the third focuses on local issues in Mainland China and Hong Kong. The book contains contributions from renowned experts in the field of financial regulation including Douglas Arner, Jeffery Carmichael , Robin Hui Huang, Dirk Schoenmaker, Andrew Sheng and Michael Taylor allowing for authoritative and interdisciplinary analyses"--
"In light of on-going global financial crises, the institutional structure of financial regulation is currently a subject of significant academic and practical interest. The financial crisis has called into question the adequacy of financial regulation at the national and supranational levels, and has instigated financial regulatory reforms in major markets overseas. This has included the enactment of the Dodd-Frank Act in the US, and the program to split the Financial Services Authority in the UK. This book examines the institutional structure reform of financial regulation from a comparative perspective, exploring both fundamental theories and international experiences. The book explores the three main institutional structures of financial regulation in the world; the sectors-based model, adopted in the US, Mainland China and Hong Kong; the twin-peaks model with Australia and the Netherlands as its pioneers; and the single-regulator model as represented by the former Financial Services Authority in the UK and the Financial Services Agency in Japan. The book contains contributions from renowned experts in the field of financial regulation including Douglas Arner, Jeffery Carmichael, Robin Hui Huang, Dirk Schoenmaker, and Michael Taylor, and will be of interest to students and researchers of banking and finance law, and comparative economics"--
Includes bibliographical references and index.
rpm 24/10/2017
Loans
Keywords: Financial institutions--Law and legislation; Financial institutions--Government policy; Finance--Law and legislation; Financial institutions--State supervision; International finance--Law and legislation; Financial services industry--Law and legislation